Victory in Tragic Ending: Analysis of Sophoclesâ€™ "Oedipus The King" (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
This study aims on revealing the concept of victory through the Tragical ending which reflected from Oedipus the King drama written by Sophocles. The objectives of this study are to explain How the concept of Victory in Tragic ending described in Sophoclesâ€™ Oedipus the King. This study is a qualitative study which applied Straussâ€™ Structuralism Theory and used discourse instrinsic elements of drama approach. The objects of this study include the material objects which are the drama â€œOedipus the Kingâ€ written by Sophocles as well as formal object which is the intrinsic elements of drama, such as dialogue, staging, characters, plot and themes which reflected from the dialogue in the drama. The data of this study is a qualitative data which is in the form of dialogues on the drama. From the data analysis, it was found that (1) intrinsic elements of drama analysis such as, dialogue, staging, character, plot and themes put a contribution. The contribution of the dialogue, staging, character, plot and themes is considered as a result of the supportive data which the writer used to analyze the main goal of this analysis using Straussâ€™ binary oppposition. (2) By the Straussâ€™ Binary Opposition, it appears that both of protagonist and antagonist of the story which this case between Oedipus and Teireisias shows their own figure. In the end, Teireisias who had a limited vision and the bad words when he talks to Oedipus, he has the knowledge behind his lackness and his knowledge is categorized as divine knowledge, since his every words he said was proven in the last of the story. (3) Concept of victory that the writer discovered after doing the binary opposition between Oedipus and Teireisias, then from the Oedipusâ€™ oppositions the writer seeks the evidence that behind all of the Oedipus weakness againtsTeireisias, there still a concept of winning or victory. These evidences was obtained through the dialogues which occured in the tragic ending of Oedipus of the King Drama and shows that the tragic ending in Oedipus the King story writtten by Sophocles were symbolized as Victory. Keywords: Intrinsic elements, drama, Binary Opposition, Structuralism